Bio-inspired biorthogonal compartmental microparticles for tumor chemotherapy and photothermal therapy - Qingfei Zhang; Gaizhen Kuang; Li Wang; Lu Fan; Yechao Zhou; Luoran Shang; Yuanjin Zhao; Weijian Sun (Journal of Nanobiotechnology, 2024)
Abstract Microcarrier is a promising drug delivery system demonstrating significant value in treating cancers. One of the main goals is to devise microcarriers with ingenious structures and functions to achieve better therapeutic efficacy in tumors. Here, inspired by the nucleus-cytoplasm structure of cells and the material exchange reaction between them, we develop a type of biorthogonal compartmental microparticles (BCMs) from microfluidics that can separately load and sequentially release cyclooctene-modified doxorubicin prodrug (TCO-DOX) and tetrazine-modified indocyanine green (Tz-ICG) for tumor therapy. The Tz-ICG works not only as an activator for TCO-DOX but also as a photothermal agent, allowing for the combination of bioorthogonal chemotherapy and photothermal therapy (PTT). Besides, the modification of DOX with cyclooctene significantly decreases the systemic toxicity of DOX. As a result, the developed BCMs demonstrate efficient in vitro tumor cell eradication and exhibit notable tumor growth inhibition with favorable safety. These findings illustrate that the formulated BCMs establish a platform for bioorthogonal prodrug activation and localized delivery, holding significant potential for cancer therapy and related applications. Graphical Abstract